Implementation Of Order E-Points As A Strengthening Implementation Of Character EducationAt State Vocational High School 1 Wonoasri - Wiyati, Wiwik (Universitas Malikussaleh, 2021)
Character education is needed today by industry in building a work culture to increase productivity. State vocational high school 1 Wonoasri as a vocational education that prepares graduates to be ready to work has made efforts to strengthen character education through ketarunaan education. Ketarunaan education aims to instill the character values and nationalism of students. E-points or electronic points are points that can be inputted digitally and stored in a database.The study was aimed: 1) to describe the application of order e-points in the implementation of strengthening character education at state vocational high school 1 Wonoasri ; 2) to describe the significance of the effect of the application of order e-points on changes in the behavior of students at state vocational high school 1 Wonoasri. The data taken are class X and class XI in the period July to December 2018 and January to December 2019. Specifically, class XI data is taken when students have not implemented Fieldwork Practices starting in October each year. The results of the data from the e-points application note that: 1) the total number of students in class X and class XI in 2018 amounted to 1186 people, who violated the rules of discipline of 531 people or 44.77%. In 2019, there were 1186 students who committed violations amounting to 133 people or 11.21%. The number of students who committed violations in 2019 when compared to 2018 decreased by 33.56%; 2) The application of e-points has a significant impact on changes in the attitudes and character of students towards the better. The indicator is a decrease in the number of violations committed by students.